Malaysians’ Perception Towards Electronic Word-Of-Mouth (Ewom) And Online Social Network Advertisements For Travel Planning - Low, Way Anne (Universiti Malaysia Sarawak (UNIMAS), 2017)
The aim of this study is to understand and identify the roles of electronic word-of-mouth (eWOM) and online social network advertisements in influencing the consumer online social network usage intention for travel planning among Malaysians. The independent variables used in this study are electronic word-of-mouth (eWOM) and online social network advertisements, with emotional state as the mediator and consumer online social network usage intention for travel planning as the dependent variable. Survey questionnaire is the research instrument that is utilized in this study to obtain data from the targeted sample size, which is 400 Malaysian respondents. The actual data collection of this study was carried out by posting and sharing the online questionnaire to 400 Malaysian users on Facebook. Statistical Package of Social Sciences (SPSS) version 22 software was implemented to analyze the data collected, by using Descriptive Statistics, Reliability Analysis, Correlation Coefficient Analysis and Simple Linear Regression Analysis. The three hypotheses stated in this study are accepted, where the results showed that there are significant relationships between electronic word-of-mouth (eWOM) and emotional state, between online social network advertisements and emotional state, as well as between emotional state and consumer online social network usage intention for travel planning